Quotation marks in advanced language acquisition: A reading time experiment on English pure quotation - Schlechtweg , Marcel (Linguistik Online, 2022)
Quotation marks represent a well-known tool to refer to something in a metalinguistic way. For instance, in the sentence “Gold” is a concrete noun, we focus on a linguistic property of the noun gold rather than, or at least in addition to, its standard denotation, which is, in turn, referred to in a sentence like Gold is a strong metal. While the semantic and pragmatic characteristics of quotation in general and quotation marks in particular are relatively well understood, we know much less about whether and how one uses, processes, and acquires these marks. The present article aims at connecting to and expanding previous research on the perception and production of quotation marks and concentrates on the role quotation marks play in the detection of English pure quotation in advanced readers. We show that quotation marks are relevant in advanced language acquisition, and that individuals benefit from the marks when being exposed to quotational constructions.